How International Are the Top International Journals of Criminology and Criminal Justice? - Faraldo Cabana, Patricia (European journal on criminal policy and research, 2021)
The purpose of this paper is to assess the level of international, non-Anglo-American involvement in the editorial boards and content of the leading international journals of criminology and criminal law to investigate a reported bias against non-Anglo-American material. The research employed editorial board and content analysis of ten leading journals of criminology and criminal law, selected because of their international involvement according to their own aims and scope’s description. Most of the ten journals were found to have low levels of international involvement, with high proportions of both Anglo-American authors and data, and Anglo-American membership of editorial boards. The editorial board analysis also revealed institutional links with journal boards and a network of overlapping membership between the editorial boards. This suggests the existence of networks of Anglo-American scholars who are naturally inclined to favour research that fits their worldview. Such networks create a hierarchy of knowledge that favours the one produced in the US and the UK and promotes the scientific success of Anglo-American scholars and contents. However, although the shadow of Anglo-American dominance continues to lie over the two fields, there is also evidence of increasing research and authorship diversity. Perhaps, we are entering a new era of research internationalism.